Conservation of cattail, Typha domingensis (Typhaceae) forage: Silage and hay (UNED Research Journal, 2018)
Integrating the management of the southern cattail into cattle feeding practices provides, from a management perspective, keeping water mirrors for birds, and, for producers, a food source for ruminant animals when low rains reduce forage growth. We determined the suitability of the plant as hay or silage after four months of re-growth. For hay, we dried the forage in sunlight from 10AM to 2PM for 4 days. In the case of silage, we added 3% w/w molasses, and tried three levels of urea (0.5, 1 and 1.5% w/w) at a constant level of molasses (3% w/w). This hay has a better crude protein and IVDMD profile than previously reported values for Transvala hay, cattail hay is an acceptable alternative source of forage near the wetland. Silage has a suitable behavior when exposed to an anaerobic fermentation, which together with the addition of urea and molasses, preserves and increases nitrogen.
Keywords: Dehydration; anaerobic fermentation; crude protein; digestibility; wetland